Treating Asthma in Pregnancy - An Update (Faridpur Medical College Journal, 2014)
Asthma is one of the most common chronic medical conditions affecting the lungs during pregnancy. At any given time, up to 8% pregnant women have asthma. During pregnancy, asthma not only affects the woman, but it can also cut back on the oxygen to fetus. But this does not mean that having asthma will make pregnancy more difficult or dangerous to fetus. Pregnant women who have asthma that is properly controlled generally have normal pregnancies with little or no increased risk to pregnant women or their developing babies. Currently available national guidelines for the treatment of asthma during pregnancy emphasize the objective measurement of control, patient education, motivation, caution and medication adherence. The article reviews the available literature highlighting the appropriate selection of medications in the treatment of asthma during pregnancy, and to identify those factors which may influence the asthma care provider's ability to successfully manage this condition, and also illustrate that maintaining asthma control with long term medications in pregnancy is safer than the risk of uncontrolled asthma or untreated exacerbations for both the mother and the fetus. Women's drug treatment during pregnancy should be regularly assessed in the light of asthma control criteria. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20392 Faridpur Med. Coll. J. 2013;8(2): 85-91